Information systems security and privacy : second International Conference, ICISSP 2016, Rome, Italy, February 19-21, 2016, Revised selected papers /: second International Conference, ICISSP 2016, Rome, Italy, February 19-21, 2016, Revised selected papers. (2017) - Unknown
No abstract available